Inhibition of RXR and PPARγ ameliorates diet-induced obesity and type 2 diabetes - Yamauchi, Toshimasa (American Society for Clinical Investigation, 2001)
PPARγ is a ligand-activated transcription factor and functions as a heterodimer with a retinoid X receptor (RXR). Supraphysiological activation of PPARγ by thiazolidinediones can reduce insulin resistance and hyperglycemia in type 2 diabetes, but these drugs can also cause weight gain. Quite unexpectedly, a moderate reduction of PPARγ activity observed in heterozygous PPARγ-deficient mice or the Pro12Ala polymorphism in human PPARγ, has been shown to prevent insulin resistance and obesity induced by a high-fat diet. In this study, we investigated whether functional antagonism toward PPARγ/RXR could be used to treat obesity and type 2 diabetes. We show herein that an RXR antagonist and a PPARγ antagonist decrease triglyceride (TG) content in white adipose tissue, skeletal muscle, and liver. These inhibitors potentiated leptin’s effects and increased fatty acid combustion and energy dissipation, thereby ameliorating HF diet-induced obesity and insulin resistance. Paradoxically, treatment of heterozygous PPARγ-deficient mice with an RXR antagonist or a PPARγ antagonist depletes white adipose tissue and markedly decreases leptin levels and energy dissipation, which increases TG content in skeletal muscle and the liver, thereby leading to the re-emergence of insulin resistance. Our data suggested that appropriate functional antagonism of PPARγ/RXR may be a logical approach to protection against obesity and related diseases such as type 2 diabetes.